Diary of a wimpy kid; Rodrick rules - Kinney,Jeff (Penguin, 2015)
Greg Heffley tells about his summer vacation and his attempts to steer clear of trouble when he returns to middle school and tries to keep his older brother Rodrick from telling everyone about Greg's most humiliating experience of the summer.